Energy poverty in Portugal: which households are the most vulnerable? - Pocinho, Maria Dias (2021)
: Energy poverty affects the health and wellbeing of households and contributes to poverty traps. In 2018, 20 percent of Portuguese households mentioned being unable to keep their home adequately warm. The results of a logit model using 2018 EU SILC data show that younger, less educated tenants living under poor dwelling conditions are among the most vulnerable in Portugal. Although energy poverty is directly linked to income poverty, not all poverty policies have been successful in solving both problems at the same time. Proper identification of those affected and associated socio-economic consequences is vital for adequate policy design.